PENGGUNAAN LIDAH BUAYA (Aloe vera) SEBAGAI KOAGULAN ALAMI UNTUK MENURUNKAN KEKERUHAN AIR - January, Elly; Putra, Heri Shatriadi Chandra; Zairinayati, Zairinayati (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2021)
Dug wells are the most widely used clean water facilities in the community, but they often have high turbidity levels. So that processing must be done using a coagulant material. Aloe vera is a natural ingredient that contains complex carbohydrates, sugars, and mucilages which can bind particles in water. This study aims to determine the effect of variations in Aloe vera doses on reducing water turbidity. This study used a completely randomized design (CRD) with three dose variations (0.1 ml, 0.2 ml, and 0.3 ml) and six repetitions. A total of 500 ml of raw water from resident wells was used for each treatment. The results showed that at a dose of 0.1 ml, the turbidity decreased by 3.7%, from 41.1 NTU to 39.6 NTU (SD = 0.54). The dose was 0.2 ml, decreased by 6.8% (38.3 NTU; SD = 1.54), and the dose was 0.3 ml decreased by 13.9% (35.4 NTU; SD = 1.02). Statistically, it showed a significant difference in turbidity in each treatment group (p-value <0.05). Research has shown that Aloe vera can be used as a natural coagulant, but further research is needed to determine the correct dosage.